Diagnostic yield of CTPA and Wells Score utilization in pulmonary embolism assessment: experience from a Malaysian tertiary hospital - Ahmad, Nur Fathihah; Md Ralib @ Md Raghib, Ahmad Razali (Malaysian Medical Association, 2026)
Introduction: Computed Tomography Pulmonary Angiography (CTPA) is the gold standard for diagnosing pulmonary embolism (PE), though concerns about overuse persist. Materials and Methods: This study evaluated CTPA yield and Wells Score use in 361 adults at a Malaysian tertiary centre (May 2017–July 2021). Results: PE was confirmed in 29.6% of cases, above international benchmarks. While the Wells Score was applied in 78.5% of cases, only 32.1% adhered strictly to local guidelines. Conclusion: CTPA was not overutilized, but there is a gap between recommended clinical pathways and real-world decision-making, highlighting the need to standardize practice to improve diagnostic efficiency and support evidence-based care.